Menakar Konstitusionalitas Penundaan dan/atau Pemotongan Anggaran Transfer ke Daerah dalam UU APBN - M Beni Kurniawan (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
Provisions regarding delays and/or withholding of transfers to regions by the Government in the APBN Law create problems when they are considered to create legal uncertainty regarding finances, which should be the domain of regional governments. This study aims to analyze: the constitutional urgency of the existence of a transfer budget to the regions from the center and the suitability of the sanctions for delaying and/or cutting budget transfers to the areas in the APBN Law. The study results show that transfers to the regions are a form of constitutional embodiment in the form of handing over financial resources to the areas as an actualization of effective fiscal decentralization. However, in practice, some regions do not comply with budget allocations, so the implications for regional financial management are not on target. On the other hand, the provision of sanctions for delaying and/or withholding funds transfers to the regions is in line with the financial construction of the unitary state with a decentralized system. This has also been strengthened through Constitutional Court Decision No. 5/PUU-XVI/2018.